Isolation and Identification of Bacteria Associated with Bladder Cancer Patients - Al-Bayati, Avan H.; Guirges, Sami Y.; Al-Dabbagh, Rassool A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Several biological factors such as bacterial infections and immunological status are implicated in predisposing individuals to bladder cancer. Bacterial infection of urinary tract has been related to increase the risk of bladder cancer.Patients and Methods: Resected tumors of a total of 73 patients were obtained under sterile surgical conditions. Biopsy processing samples and culture procedures of biopsy samples were mentioned in the text.Results: Bacterial growth was observed in 48 biopsy tissues of those patients represent (65.8%) while, 25(34.2%) yielded no growth (negative results). It is obvious that E. coli is the most predominant organisms followed by K. pneumoniae and Ps. Aeruginosa. The other uropathogens isolated more or less of equal distribution.Conclusion: High frequency and great variety of bacteria in cystectomy specimens removed from cancer of urinary bladder. They were often Gram-negative pathogens (primarily Enterobacteriaceae).